Algonormative expectations - Germano Schwartz; Renata Almeida da Costa (Oñati Socio-Legal Series)
Contemporary society has developed, for itself, a way of reducing its own complexity: algorithms. Their basic function is precisely that of reducing the complexity of expectations – cognitive and normative – and those of the expectations of expectations (juridical decisions).  When observed under this lens, algorithms, by way of their artificial communication, equally influence normative expectations (Luhmann) and juridical norms (Hydén). In this article we will attempt to respond to the following question: is it possible to defend the existence of algonormative expectations? In order to respond, methodologically, one seeks to define in what way the employment of the theories of these authors contribute to the development of the concept of algonormative expectations. It is in this direction that one initially approaches Hydén’s bases for algo norms and, at a second stage, one seeks to conjugate them with Luhmannian cognitive expectations. The final question is to verify, alongside the artificial intelligence defended by Esposito, what the conditions are for the observation of algonormative expectations.